Development and validation of Muslim moral emotion inventory among Malay youth in the Klang Valley, Malaysia - Sawai, Rezki Perdani (2019)
Moral emotions of shame and guilt play an important role in shaping the moral/prosocial behaviour of youth. Many of the existing instruments that measure such emotions have been developed from and reflect Western perspectives and cultures. Differences in the concepts of shame and guilt and the lack of measurement tools for measuring them based on Islamic perspectives has hindered efforts to understand the moral emotions of youths and how they shape their moral/prosocial behaviour. This study was conducted to 1) provide an understanding of shame and guilt based on Islamic perspectives; 2) develop a tool for measuring shame and guilt; 3) ascertain the reliability and validity of the measurement instrument and 4) establish the norm for youth's moral emotions. This study employed an exploratory sequential mixed-method research (MMR) design in order to broadly explore and understand the moral emotions of shame and guilt of youths based on Islamic perspectives. This study is divided into three phases namely design, development and evaluation. The first phase involves qualitative studies to achieve the first objective of the study through (i) content analysis of Quranic verses and hadiths related to shame and guilt; and (ii) interviews with experts to understand the concept of shame and guilt from an Islamic perspective. From the results of the content analysis and expert interviews, themes related to shame and guilt were used to develop instruments for measuring those emotions. The definitions of the concept are derived from literature studies based on traditional Islamic sources such as the Quran and hadith, and the classical writings of Islamic moralists such as Ibn Miskawayh, al-Ghazali and contemporary Islamic scholars. Based on the content analysis, literature review and expert interviews, a Muslim Moral Emotions Inventory (MMEI) was developed. At the instrument development stage, the researcher adopted a quantitative approach through the application of the DeVellis (2012) and Miller et al. (2013) models. Once the measurement instrument was constructed, the validity test, content and reliability analysis was conducted through a pilot test to determine the validity and reliability of the measurement instrument. The results show that the MMEI is valid and reliable. Later, the MMEI was tested in the field among 1147 Malay Muslim youths from three institutions, i.e., Tahfiz, higher educational institution students and inmates of rehabilitation centres in Klang Valley. The scores obtained were used to establish the norms and benchmarks of the moral emotions of the youths. Following that, the MMEI was also tested using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to determine the validity of the construct. The EFA results show five basic dimensions of MMEI that constitute shame, namely positive speech, sensitivity to others' judgments, lowering or maintaining their view, preserving one's purity/dignity and modest self-presentation. The results of this study also found four basic dimensions of MMEI that build on guilt, fear of punishment, concern for others, God consciousness and forgiveness. The EFA revealed that the Barlett Sphericity Test had a significant relationship at χ2 (276) = 4897.39, p = .001. A total of 26 items was retained for the Shame construct and 21 items for the Guilt construct. Subsequently, validation factor analysis (CFA) using AMOS 22 noted that the compatibility value for Shame was p = .000, RMSEA = .041, GFI = .957, CFI = .973, RFI = .926 and Chisq/df = 1.815. On the other hand, for the Guilt construct it is p = .000, RMSEA = .051, GFI = .963, CFI = .974, RFI = .935 and Chisq/df = 2.296. The findings of this study show that the instruments developed are valid and appropriate for measuring shame and guilt among youth. This study contributes to the theoretical implications as well as the Islamization of science. In addition, it is envisaged that the MMEI instrument will assist towards promoting positive aspects in the moral development of youth.